2023
DOI: 10.1108/ijpl-05-2022-0025
|View full text |Cite
|
Sign up to set email alerts
|

Servant leadership and employee's job performance: the role of public service motivation in Ethiopian public sector organizations

Abstract: PurposeThis study aims mainly to examine the mediating role of public service motivation (PSM) in the relationship between servant leadership and employee performance in the context of Ethiopian public sector organization employees.Design/methodology/approachA survey design has been used, where all the 154 employees from seven public sector organizations participated. A confirmatory factor analysis employed on the 149 valid responses further validated the hypothesized model.FindingsThe study supported the sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The result suggests that an ethically competent public servant tends to align with the organizational ethical standards of their work, becoming more involved with the institution they work for and, consequently, more committed to it. And this is reinforced when the leader of public servants is ethical, being a model to be followed, as the ethical competencies of public servants are valued and encouraged (Koay and Lim, 2021; Mishra and Hassen, 2023).…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result suggests that an ethically competent public servant tends to align with the organizational ethical standards of their work, becoming more involved with the institution they work for and, consequently, more committed to it. And this is reinforced when the leader of public servants is ethical, being a model to be followed, as the ethical competencies of public servants are valued and encouraged (Koay and Lim, 2021; Mishra and Hassen, 2023).…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Employees committed to the organization tend to demonstrate greater acceptance of the organization's values and objectives, are more likely to accept leaders who adhere to ethical beliefs and values (Koay and Lim, 2021) and can deal with adverse ethical situations (Andersson et al, 2022). Ethical leadership tends to make public servants develop their ethical competencies, as the leader is a model for the ethical behavior of public servants IJPL 20,1 (Qing et al, 2020;Mishra and Hassen, 2023). Considering these studies, we assume that individuals with ethical competence engage more with the organization, becoming more committed to it as they identify with its principles and values.…”
Section: Competencies Of the Public Servantmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the research problem in this study is how public service motivation plays a role in improving ASN performance and how innovative behavior influences ASN performance, both directly and indirectly. Furthermore, referring to previous research, it has been found that public service motivation significantly contributes to various aspects, including the enhancement of innovative behavior (Lesmana et al, 2022;Nguyen et al, 2022) and has a positive impact on individual performance (Fan et al, 2022;Mishra & Hassen, 2023;Putri & Fachmi, 2022;Schwarz et al, 2020). However, this contrasts with other research that, although public service motivation influences innovative behavior and individual performance, the impact of public service motivation on innovative behavior is only 32.3% (Wicaksono & Lesmana, 2022); and on performance, it is relatively low at 26.1% (Kristanti & Eko Yudiatmaja, 2022).…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, recent research in Ethiopia, Africa, suggests that high public service motivation can enhance employee performance in providing better services to the public (Mishra & Hassen, 2023). Other studies explain the relationship between public service management and individual performance (Fan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%